El impacto de la actualización tecnológica en la competitividad de las empresas cárnicas de Cuenca (Estudios) - González González, Christian (2025)
Innovation, when considered from the perspective of market interests, aims at the introduction of novelties in a product or the development of a new one. However, with regard to technology, innovation must be viewed beyond the practices of continuous improvement merely focused on process transformation. Instead, it should be seen as a value-generating contribution that drives competitiveness. Meat organizations should follow the same innovation processes as other companies, implementing technological, organizational, financial, or commercial alternatives. Nevertheless, some meat companies often fail to differentiate themselves from competitors due to a lack of application of innovative strategies or processes. In this context, the research presents the reality of meat companies in Cuenca, for which a survey was conducted to determine the influence of their innovation on value management related to competitiveness. The validation process of variable behavior was carried out using the Shapiro-Wilk statistic, and subsequently, through a relational scope and the Spearman test, the relationship between the study variables was demonstrated. The main results show that, statistically, business innovation has a significant impact on the competitiveness of Cuenca’s meat companies and that these companies are indeed constantly innovating.